2021
DOI: 10.1186/s40902-021-00296-5
|View full text |Cite
|
Sign up to set email alerts
|

The effects of orthognathic surgery on auditory function

Abstract: Background Orthognathic surgery is widely used in treating functional and skeletal problems. Any surgical procedure could cause side effects. Objectives This study aimed to evaluate the potential changes in orthognathic surgery on the hearing function of patients. Materials and methods Thirty-one orthognathic surgery candidates were recruited in this study. Patients underwent either single or double ja… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 13 publications
0
2
0
Order By: Relevance
“…11 Other studies also reported a risk of minor changes in the hearing function during the first week after orthognathic surgery, but these changes either disappeared completely or remained at negligible levels. 12…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…11 Other studies also reported a risk of minor changes in the hearing function during the first week after orthognathic surgery, but these changes either disappeared completely or remained at negligible levels. 12…”
Section: Discussionmentioning
confidence: 99%
“…11 Other studies also reported a risk of minor changes in the hearing function during the first week after orthognathic surgery, but these changes either disappeared completely or remained at negligible levels. 12 Failure to form an adequate bony bridge at the osteotomy site may result in the fibrous union, which is thought to result in nonunion. In this study, 2 patients showed maxillary nonunion.…”
Section: Discussionmentioning
confidence: 99%